The effectiveness of topical Arnebia euchroma Oil in the treatment of Pressure Ulcer: A Case Report: Arnebia euchroma Oil in the treatment of Pressure Ulcer - Mohhamadi Kenari, Hoorieh; Erabi, Sakineh; Ghobadi, Ali (Journal of Contemporary Medical Sciences, 2022)
Decreased tissue blood flow causes pressure ulcers due to prolonged pressure on the area, which becomes problematic for immobile individuals. The medical community has often been involved in curing such a problem in individuals with disabilities and immobility. To alleviate this problem, therefore, plenty of investigations are always seeking novel methods. Furthermore, herbal plants are increasingly used owing to the accepted status of plant-derived drugs in recent years. Our female case aged 52 years that was referred to the wound clinic complaining sensory and motor weakness of the upper extremity and sudden paralysis of the lower extremity as of 1 year ago, which was diagnosed as myelitis. She complained of two wounds on both sides of the right and left buttocks with a size of 9 × 5 and another 6 × 4.5 cm from 3 months ago, and a wound with a size of 5 × 4.5 in the sacral area (sacrum) from 20 days prior to the admission. There was tissue necrosis without muscle engagement, osteomyelitis, or tunneling; besides, nasty odors and sludge were absent accounted for in class 3 in the group of wounds. She received starting therapy using Arnebia euchroma oil. As of the 2nd week onward, she was treated very successfully, and the complete wound healing occurred in 8 weeks. The use of A. euchroma for wound healing and reducing infection and inflammation can greatly contribute to the cure of pressure ulcers and can be properly suggested in healing these ulcers.